Magnetic Resonance Imaging Correlates of Multiple Sclerosis Immunopathological Patterns. Issue 3 (19th July 2021) - Metz, Imke; Gavrilova, Ralitza H.; Weigand, Stephen D.; Frischer, Josa M.; Popescu, Bogdan F.; Guo, Yong; Gloth, Mareike; Tobin, William Oliver; Zalewski, Nicholas L.; Lassmann, Hans; Tillema, Jan M.; Erickson, Bradley J.; et al.
Abstract : Objective: Histology reveals that early active multiple sclerosis lesions can be classified into 3 main interindividually heterogeneous but intraindividually stable immunopathological patterns of active demyelination (patterns I–III). In patterns I and II, a T‐cell‐ and macrophage‐associated demyelination is suggested, with pattern II only showing signs of a humoral immune response. Pattern III is characterized by inflammatory lesions with an oligodendrocyte degeneration. Patterns suggest pathogenic heterogeneity, and we postulated that they have distinct magnetic resonance imaging (MRI) correlates that may serve as biomarkers. Methods: We evaluated in an international collaborative retrospective cohort study the MRI lesion characteristics of 789 conventional prebiopsy and follow‐up MRIs in relation to their histopathologically classified immunopathological patterns (n = 161 subjects) and lesion edge features (n = 112). Results: A strong association of a ringlike enhancement and a hypointense T2‐weighted (T2w) rim with patterns I and II, but not pattern III, was observed. Only a fraction of pattern III patients showed a ringlike enhancement, and this was always atypical. Ringlike enhancement and T2w rims colocalized, and ringlike enhancement showed a strong association with macrophage rims as shown by histology. A strong concordance of MRI lesion characteristics, meaning that different lesions showed the same features, was found when comparing biopsied and nonbiopsied lesions at a given time point, indicating lesion homogeneity within individual patients. Interpretation: We provide robust evidence that MRI characteristics reflect specific morphological features of multiple sclerosis immunopatterns and that ringlike enhancement and T2w hypointense rims might serve as a valuable noninvasive biomarker to differentiate pathological patterns of demyelination. ANN NEUROL 2021;90:440–454